A literature analysis on the living environmental elements in residential areas - Rosli, Nur Shazwani; Kadar Hamsa, Abdul Azeez (2012)
Residents are increasingly faced with poor living environment as a result of deterioration in the urban environment. Increasing traffic volume, traffic noise, traffic congestion, and air pollution are few among the many living environmental elements that the residents are subjected to which affect the quality of life and well-being of the community in the long run. A liveable residential neighbourhood is one that offers peaceful, harmonious, and healthy environment for the benefits of the community. Urban environments that are designed to achieve sustainable design principles will encourage people to reduce their car use and choose more sustainable modes for their travel activities. The purpose of this paper is to discuss on the living environmental elements that contribute to the well-being of the residents. It focuses on analysis of literature in establishing a framework on sustainability for understanding the relationship between the quality of an urban environment and the benefit to the community. In the process of planning health-promoting urban environments, it is essential to provide better living environment which can offer relief from environmental stress and opportunities and at the same time striving to minimise the negative impacts of urbanisation in the residential areas.